Why Your Patient May Need an ACL Reconstruction Plus Lateral Extra-Articular Tenodesis Procedure - Amit Momaya; Chandler Harris; Matt Hargreaves (North American Sports Medicine Institute, 2024)
Anterior cruciate ligament (ACL) tears are one of the most common knee injuries experienced by active individuals engaging in cutting sports. Despite improved surgical techniques and rehabilitation, the return to sport rate and re-tear rates remain unsatisfactory. Lateral extra-articular tenodesis (LET) is a procedure that has been growing in interest when performed in conjunction with ACL reconstruction. The benefits of adding an LET procedure to an ACL surgery may include greater rotational stability, decreased re-tear rates, and improved return to play. Level of evidence: V